Stenting for symptomatic high-grade basilar artery stenosis - Ćulafić Slobodan; Lakićević Novak; Mihajlović Miodrag; Stefanović Dara; Spaić Milan (Vojnosanitetski Pregled)
Background. Stenosis of brain vessels in 5-10% of cases causes ischemic disesase of the brain. Atherosclerosis is a cause of stenosis in 95% of cases. Patients with basilar artery stenosis and recurrent ischemic attacks are candidate for stroke in 50% of cases in the first two years. Case report. A 48-year old man presented with a 12-month history of transitory ischemic attacks, periodical loss of vision and balance disorder. Diagnostic cerebral angiography performed by MSCT revealed annular stenosis of basilar artery (85%). Digital subtraction angiography (DSA) confirmed dimensions, grade and localisation of stenosis. Endovascular stenting was performed in general anesthesia. The first step of procedure was preliminary balloon angioplasty and after that self- expandable stent (diameter of 3.0 mm, length of 12 mm) was placed. Check angiogram after stenting confirmed complete dilatation of basilar artery stenosis. Conclusion. Combination of balloon angioplasty and selfexpandable stenting made possible non-surgical treatment of simptomatic basilar artery stenosis.